Prevalence of hepatobiliary dysfunction and ultrasonographic abnormalities in dengue fever in pediatric age group - Dr. Madhusudan S.R.; Dr. Prabhavathi R; Dr.Suman M.G.; Dr. Govindaraj M.; Dr. Puttaswamy M. (Pediatric Review: International Journal of Pediatric Research, 2019)
Introduction: High morbidity and mortality in DF/DHF is due to multiorgan involvement. Hepatic involvement can present with varied manifestations ranging from hepatomegaly to fulminant hepatic failure. Incidence of hepatic dysfunction is more in Dengue shock syndrome and Dengue hemorrhagic fever. Ultrasound can be used as a prognostic indicator and also used as means of monitoring for plasma leakage. Objectives: To study the clinical presentation, hepatic abnormalities and the ultrasonographic findings in dengue fever, dengue haemorrhagic fever and dengue shock syndrome and to correlate these findings with the severity of dengue fever. Materials and Methods: 100 hospitalized patients of Dengue fever were classified as DF/DHF/DSS as per their clinical manifestations. Lab investigations namely SGOT, SGPT, PT, APTT and INR were monitored. Ultrasonography of the abdomen and thorax were done. Hepatic enzymes, coagulation workup and ultrasonographic parameters in DF/DHF/DSS were compared in the study. Conclusion: Severe dengue can pose challenges to the treating physician. Hence early identification of deterioration in the clinical status can be reasonably assessed by using hepatic and ultrasound parameters which will help in the management of dengue illness and thus reducing the mortality and morbidity.